Ta’lim, Tazkiyah, dan Tarqib dalam Memperbaiki Ibadah Peserta Didik - Marzuki, Darlina Nuralisyarifah; Rivauzi, Ahmad (Darul Yasin Al Sys, 2023)
The problem in this research is the Islamic religious education teachers to improve students’ worship, because there are still many students’ religious practices, especially prayers, that are still lacking in implementation. So Islamic religious education teachers carry out efforts in the form of: 1) Islamic religious education teachers provide ta’lim or religious learning, to student throught the learning process in the classroom and outside the classroom. 2) Islamic religious education teachers instill tazkiyah or awareness, about the importance of worship in students using efforts in the form of example, habituation, advice, and punishment. 3) the Islamic religious education teachers carries out tarqib or supervision, of students’ worship. The aim of this research is to find out how Islamic religious education teachers ta’lim, tazkiyah, and tarqib improve students’ worship. The research method used is qualitative research, whith the type of field research, the focus or core of this research is how to apply ta’lim, tazkiyah, and tarqib of Islamic religious education teachers in improving students’ worship. The types of this research are data in the form of primary data and secondary data, an the information obtained is data resulting from field observations and interviews with informants. The informants in this research include Islamic eeligious education teachers and MAN 5 Agam students. The results of this research are that the implementation of ta'lim (learning about worship), tazkiyah (awareness of the importance of worship), and tarqib (supervision of worship) carried out by Islamic religious education teachers can improve students' worship.